LEVERAGING THE MYERS-BRIGGS TYPE INDICATOR (MBTI) TO EVALUATE STUDENT GROUP SUCCESS IN PROJECT-BASED LEARNING - Beenish Bangash (Policy Research Journal, 2025)
This study explores the application of the Myers-Briggs Type Indicator (MBTI) in assessing the success of student groups within a project-based learning (PBL) environment. By analyzing personality types and their impact on group dynamics, the research aims to identify patterns that contribute to effective collaboration and overall project success. The findings provide valuable insights for educators to optimize group formation and enhance learning outcomes by considering students' personality traits. This study highlights the potential of MBTI as a tool for improving teamwork and performance in educational settings.